Small‐Sized Bimetallic CuPd Nanoclusters Encapsulated Inside Cavity of NH2‐UiO‐66(Zr) with Superior Performance for Light‐Induced Suzuki Coupling Reaction. Issue 12 (14th August 2018) - Sun, Dengrong; Xu, Mengpeng; Jiang, Yongteng; Long, Jinlin; Li, Zhaohui
Abstract: Bimetallic CuPd nanoclusters with a small size of ≈0.9 nm are encapsulated inside cavities of NH2 ‐UiO‐66(Zr) via double‐solvent impregnation, followed by a reduction process with NaBH4 . As compared with monometallic Pd@NH2 ‐UiO‐66(Zr), bimetallic CuPd@NH2 ‐UiO‐66(Zr) shows superior performance for light‐induced Suzuki coupling reaction since the introduced Cu acts as an electron mediator to facilitate the transfer of photogenerated electrons from light‐excited NH2 ‐UiO‐66(Zr) to Pd, to form electron‐rich Pd. Moreover, CuPd@NH2 ‐UiO‐66(Zr) also shows higher activity than CuPd/NH2 ‐UiO‐66(Zr), in which CuPd nanoparticles are deposited on the surface of NH2 ‐UiO‐66(Zr). The as‐obtained CuPd@NH2 ‐UiO‐66(Zr) is stable and can be applied in the coupling of a variety of substituted iodobenzenes and phenylboronic acids. The simultaneous encapsulation of metallic Pd and Cu, acting as a catalytic active site and mediator respectively, inside the cavities of NH2 ‐UiO‐66(Zr), represents a novel strategy for designing multifunctional metal‐organic framework based catalysts for light‐induced organic reactions. Abstract : CuPd@NH2 ‐UiO‐66(Zr) with small‐sized CuPd nanoclusters encapsulated inside cavities show enhanced performance for light‐induced Suzuki coupling reaction as compared with Pd@NH2 ‐UiO‐66(Zr), since the introduced Cu acts as an electron mediator to promote the transfer of photogenerated electrons in light‐excited NH2 ‐UiO‐66(Zr) to Pd to form electron‐rich Pd.